2018
DOI: 10.1111/jfb.13557
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses to swimming fatigue in juvenile largemouth bronze gudgeon Coreius guichenoti

Abstract: Stepped velocity tests were conducted on juvenile largemouth bronze gudgeon Coreius guichenoti in a swim tunnel respirometer, and oxygen consumption increased with swimming speed to fatigue and then decreased during recovery. Serum levels of total protein, glucose and triglycerides initially decreased, increased at fatigue and then decreased during recovery. Levels stabilized after 120 min, corresponding to the time necessary to recover from fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“… Fu et al (2019) analyzed the stress response of C. guichenoti after infection with Ichthyophthirius multifiliis from the aspect of gene expression. Acute handling stress can lead to changes in blood indicators, gill and kidney tissues, and even parasitic infection of C. guichenoti ( Zhao, 2014 ; Yuan et al, 2018 ). Li et al (2013) reported that only some biological functions in head kidney tissues gradually recovered after 24 h. Using MS-222, reducing temperature, or applying electrical anesthesia could reduce the stress response caused by transportation ( Zhao, 2014 ; Zhao et al, 2014 ; Zhu et al, 2015 ; Dong et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“… Fu et al (2019) analyzed the stress response of C. guichenoti after infection with Ichthyophthirius multifiliis from the aspect of gene expression. Acute handling stress can lead to changes in blood indicators, gill and kidney tissues, and even parasitic infection of C. guichenoti ( Zhao, 2014 ; Yuan et al, 2018 ). Li et al (2013) reported that only some biological functions in head kidney tissues gradually recovered after 24 h. Using MS-222, reducing temperature, or applying electrical anesthesia could reduce the stress response caused by transportation ( Zhao, 2014 ; Zhao et al, 2014 ; Zhu et al, 2015 ; Dong et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%